METASTASIS AND LOCAL INVASION PATTERN OF BLADDER CANCER IN HASAN SADIKIN HOSPITAL - Mustafa, Akhmad; Safriadi, Ferry (Indonesian Journal of Urology, 2018)
Objective: The aim of this study is to provide database about local invasion and metastasis pattern, as well as the disease characteristics of bladder cancer in Hasan Sadikin Hospital, Bandung. Material & Methods: Between January 2011 and December 2016 there were 321 cases of bladder cancer recorded in our hospital. Of all cases, 106 patients included in this study, with evident of local invasion or distant metastasis either radiologically (contrast abdominal pelvic CT scan) or pathologically. Results: The study group consist of 106 patients (86 men [81.7%], 20 women [28.3%]); with mean age of 56.78 ± 13.19 (4-76) years old. Histopathology findings of transitional cell carcinoma (TCC) consist of 82 (77.3%) patients and the atypical histology features group of 24 (22.7%) patients. Local invasion was found in 99 patients of 321 (30.8%), with the most common organ invasion to the prostate in male (n=38 [35.8%]). Lymph node metastasis were found in 47 patients (44.3%), with the most common nodal metastasis to obturator lymph nodes (n=21 [19.8%]). Distant metastasis was found in 24 patients (22.6%) with the most common site for distant metastasis was the liver (n=12 [11.3%]). In TCC group, 12 patients (63.1%) had a distant organ metastasis with nodal metastasis, whereas in atypical group, majority of the patients with distant organ metastasis (n=5 [83.3%]) had no lymph node involvement. Moreover, in transitional cell group, not all patient (n=17 [73.1%]) had local invasion of the tumor, while all patients with distant organ metastasis in atypical group (n=6 [100%]) had abdominal or pelvic wall invasion (cT4b). Conclusion: TCC is the most common pathology findings and with Prostate is the most common site for local tumor invasion. Obturator lymph nodes is the most common nodal metastasis and liver is the most common site for distant metastasis in bladder cancer.